A semi-distributed model for locating stormwater best management practices in coastal environments. (May 2017) - Johnson, R.D.; Sample, D.J.
Abstract: New regulations in Virginia and elsewhere require reduction of runoff volume and phosphorus loads after development using approved stormwater best management practices (BMPs) that favor infiltration. The flat terrain, shallow water tables, and impermeable soils present in the Coastal Plain of Virginia limit the use of many BMPs. The BMP Checker facilitates BMP siting; calculating median slope and seasonal high water table depth, soil types, and catchment size from spatial inputs, then compares catchment characteristics to constraints to predict suitable and unsuitable BMPs and phosphorous loads. This process was validated at 11 sites in the City of Virginia Beach, and then applied citywide to assess the spatial applicability of each BMP. Wet ponds that intercept groundwater and constructed wetlands (both at 74%) were the most applicable BMPs. Sheet flow to conservation area and infiltration practices (11% and 24%, respectively) were the least applicable BMPs. Results were consistent with local experience. Highlights: BMP Checker was developed to assist in BMP siting in coastal Virginia, can be applied elsewhere. The program was evaluated at 11 developed sites in Virginia Beach, VA and found to be valid. BMP Checker was run for the entire City of Virginia Beach to assess spatial applicability of BMPs.